CITELLUS VARIEGATUS RUPESTRIS ALLEN DE IZUCAR DE MATAMOROS PUEBLA - VILLA RAMIREZ, BERNARDO (Instituto Politécnico Nacional, Escuela Nacional Ciencias Biología, Laboratorio MicroBiología Experimental, CD MEXICO, DF, MEX, 1942)
Discussion on synonymy of Simulium For the state of Oaxaca the author records S canadense and S kamloopsi The presence of S hirtipes is doubtful
ANS INST BIOL
Keywords: CITELLUS VARIEGATUS RUPESTRIS ALLEN, IZUCAR DE MATAMOROS, PUEBLA; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; MAMIFEROS